2021
DOI: 10.1007/s10055-021-00574-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of visual guidance effects for 360-degree directions

Abstract: A head-mounted display cannot cover an angle of visual field as wide as that of natural view (out-of-view problem). To enhance the visual cognition of an immersive environment, previous studies have developed various guidance designs that visualize the location or direction of items presented in the users’ surroundings. However, two issues regarding the guidance effects remain unresolved: How are the guidance effects different with each guided direction? How much is the cognitive load required by the guidance?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…As suggested by the simulation results presented in Section 3.2, reducing the perceptual uncertainty improves the search performance. This finding has been overlooked in previous studies that mainly focused on visual field guidance using overt cue stimuli (Gruenefeld, Ennenga, et al, 2017a;Gruenefeld, El Ali, et al, 2017b;Danieau et al, 2017;Gruenefeld et al, 2018;Harada and Ohyama, 2022). This results in the requirement for the property of cue stimuli to improve performance in multimodal visual field guidance.…”
Section: Simulation Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…As suggested by the simulation results presented in Section 3.2, reducing the perceptual uncertainty improves the search performance. This finding has been overlooked in previous studies that mainly focused on visual field guidance using overt cue stimuli (Gruenefeld, Ennenga, et al, 2017a;Gruenefeld, El Ali, et al, 2017b;Danieau et al, 2017;Gruenefeld et al, 2018;Harada and Ohyama, 2022). This results in the requirement for the property of cue stimuli to improve performance in multimodal visual field guidance.…”
Section: Simulation Resultsmentioning
confidence: 90%
“…These experimental paradigms have recently been extended to investigate user behavior in VR. Cue-based visual search experiments in VR involve the analysis of reaction times and/or movement angles towards a target object (Gruenefeld, Ennenga, et al, 2017a;Gruenefeld, El Ali, et al, 2017b;Danieau et al, 2017;Gruenefeld et al, 2018;Schmitz et al, 2020;Harada and Ohyama, 2022). In addition, previous studies employed overt cues that directly indicated the target location, whereas we employed non-overt cues that weakly indicated them, without interfering with the visuals.…”
Section: Behavioral Data Analysis 2211 Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors have also proposed the adoption of stereoscopic 360°‐VR devices, especially for school‐level courses, as the available technological resources and time are limited. Harada and Ohyama (2022) attribute the added value of this technology to the opportunity offered to learners to explore abstract concepts freely and safely. Another advantage of low‐immersion VR solutions, like the VeeR Mini Goggles , is their inherent potential to render the virtual scenes from different angles and points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers (Harada & Ohyama, 2022; Moro et al, 2021) who have explored systematically the potential of such technologies in biomedical science instruction have identified the following advantages: (a) it reduces the mental effort (internal factor) required to recognise and process abstract structures as well as their unique elements and features, (b) it reduces the mental load (external factor) by providing learners with points of reference that facilitate the conduct of hands‐on tasks, (c) it improves visual cognition, via the repeated representations and conceptual illustrations of the real‐world context, which make certain stimuli become automatic, and (d) it enhances learners' mental capacities (working memory)—via the rich, multi‐sensory, feedback—which are needed for new knowledge and skills to be developed and acquired, respectively.…”
Section: Introductionmentioning
confidence: 99%